MiR‐185‐3p regulates nasopharyngeal carcinoma radioresistance by targeting WNT2B in vitro. Issue 12 (20th November 2014) - Li, Guo; Wang, Yunyun; Liu, Yong; Su, Zhongwu; Liu, Chao; Ren, Shuling; Deng, Tengbo; Huang, Donghai; Tian, Yongquan; Qiu, Yuanzheng
<x xml:space="preserve">Abstract</x> Aberrant microRNA (miRNA) expression contributes to a series of malignant cancer behaviors, including radioresistance. Our previous study showed differential expression of miR‐185‐3p in post‐radiation nasopharyngeal carcinoma (NPC) cells. To investigate the role of miR‐185‐3p in NPC radioresistance, CNE‐2 and 5‐8F cells were transfected with miR‐185‐3p mimic and miR‐185‐3p inhibitor, respectively. CCK‐8 assay and colony formation experiment confirmed that the expression of miR‐185‐3p affected the radioresistance of NPC cells. A negative correlation between miR‐185‐3p and WNT2B expression was observed in NPC cells and tissues. Luciferase reporter assays confirmed that miR‐185‐3p directly targeted the coding region of WNT2B. Furthermore, we found radioresistance decreased in WNT2B‐silenced NPC cells. Activation of the WNT2B/β‐catenin pathway was accompanied by epithelial–mesenchymal transition biomarker changes in NPC. We concluded that miR‐185‐3p contributed to the radioresistance of NPC via modulation of WNT2B expression in vitro.